Harmonizing the product costing methodologies of the final test process of a semiconductor company - Layugan, Jho-Anne (Animo Repository, 2023)
This integrative action research is intended to harmonize the product costing methodologies for the final test process of Company A post-merger with Company B. In August 2021, Company B became one of Company A’s wholly-owned subsidiaries. According to WallStreetMojo (n.d.), product cost refers to all those costs which the company incurs to create the product of the company or deliver the services to the customers. On the other hand, product costing methodologies pertain to how product costs are calculated. Harmonizing product costing methodologies for the final test process involves developing and implementing consistent and standardized methods for calculating final test product costs across Company A and Company B’s final test process. This process involves selecting appropriate cost accounting methods, data collection and analysis techniques, and ensuring these are applied consistently across Company A and Company B’s product costing process. This integrative action research followed the action research cycle by Coghlan and Brannick (2014) undergoing two cycles of construction, planning action, taking action, and evaluating action. All studies, discussions, and analyses were carried out collaboratively. Our first cycle involved harmonizing the product costing methodologies for the final test process of Company A and Company B. Our team collaboratively designed the new methodologies and executed them to be able to come up with new harmonized platform rates and total test seconds. Our second cycle involved carrying out changes to the initial criteria set as the guiding methodology. At the end of the two cycles, our team was able to provide the harmonized inputs to be able to come up with harmonized final test product costs.